Integration of life-cycle assessment in a multimodal building design approach. Issue 1 (1st September 2022) - Apellániz, D; Aziz, S; Weber, M; Brechenmacher, E; Ogarkova, S; Gengnagel, C
Abstract: Decades of rapid and widespread digitization of our living and working environments have not yet brought about a comprehensive qualitative improvement of our built environment in terms of sustainability and functional and aesthetic performance. The designs of the future must be much more consistently concerned with optimizing the multimodal performance of human spaces. This paper presents a design approach to implement and combine life-cycle assessment with different simulation methods such as energy efficiency, daylight analysis, acoustics, noise insulation, structural analysis and fire protection in order to provide the designer with tools to evaluate how architectural decisions affect the building performance and its environmental impacts. This approach was applied by the architecture students of a master course at the Universität der Künste Berlin. They were given the program of a building to be constructed in the Siemensstadt in Berlin and they implemented this methodology to come up with different sustainable designs. This paper also discusses the results of this course and empathizes how the implementation of simulation tools does not constrain the possibilities of the design process, but it enriches it and leads to a more sustainable built environment.